Aggregate perceptions of intrateam conflict and individual team member perceptions of team psychological contract breach : The moderating role of individual team member perceptions of team support - Cruz, Kevin S. (Colegio Oficial de Psicólogos de Madrid, 2020)
We seek to contribute to our very limited knowledge base about a relatively new type of psychological contract: team psychological contracts. We argue that aggregate perceptions of intrateam task and relationship conflict are positively associated with individual team member perceptions of team psychological contract breach. We also argue that individual team member perceptions of team support mitigate the respective relationships between aggregate perceptions of intrateam task and relationship conflict and individual team member perceptions of team psychological contract breach. Using 306 team members across 76 teams from 18 organizations, we find that aggregate perceptions of intrateam task and relationship conflict are both positively associated with individual team member perceptions of team psychological contract breach. However, we find that individual team member perceptions of team support only mitigate the relationship between aggregate perceptions of intrateam relationship conflict and individual team member perceptions of team psychological contract breach. Theoretical and practical implications are discussed.